2012
DOI: 10.1002/jcu.21920
|View full text |Cite
|
Sign up to set email alerts
|

Influence of smoking cessation on carotid artery wall elasticity evaluated by echo‐tracking

Abstract: ET can be used to evaluate quantitatively the impact of smoking cessation on common carotid artery wall elasticity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…The findings obtained in the present study confirm previous reports of increased rigidity, even at a very young age, of the large arteries in adult SMs following smoking cessation (9-16). Increased arterial stiffness could represent the predisposing cause of the higher 24-hour ABPM values in these subjects.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The findings obtained in the present study confirm previous reports of increased rigidity, even at a very young age, of the large arteries in adult SMs following smoking cessation (9-16). Increased arterial stiffness could represent the predisposing cause of the higher 24-hour ABPM values in these subjects.…”
Section: Discussionsupporting
confidence: 92%
“…Previously, arterial distensibility in SMs (during active tobacco use or passive exposure to smoke or after quitting smoking) has been evaluated using indices capable of providing an evaluation only at the time of examination; conversely, the QKd interval technique provides a complete profile of circadian variations in pulse wave velocity (9,10,37). A 24-hour evaluation would be more appropriate than a single measurement in assessing arterial elasticity (38).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We used the echo‐tracking technique to detect stiffness of the carotid artery in women with and without PE. This technique allows noninvasive assessment of local arterial stiffness by following the phase shift of the ultrasound radiofrequency signals generated by arterial wall motion . The results showed that women with PE have greater arterial stiffness than healthy controls.…”
Section: Discussionmentioning
confidence: 99%